CONCRETISATION OF THE PRINCIPLE OF SUSTAINABLE FINANCE IN THE BANKING SECTOR LEGISLATION IN INDONESIA: LON FULLER EIGHT DESIDERATA APPROACH - Dewantara, Reka; Agatha, Bimarceline (Veritas et Justitia, 2019)
This article aims is to explores an issue where  Sustainable finance itself is a form of embodiment in Article 33 paragraph (4) of the 1945 Constitution of the Republic of Indonesia that the national economy is organized based on several principles, one of which is sustainable principles by maintaining a balance and unity of the national economy. Thus Article 33 paragraph (4) of the 1945 Constitution of the Republic of Indonesia is a juridical basis of sustainable finance that promotes a sustainable financial system. The research methodology was an integration of empirical juridical research methods and interpretation of the normative method results. The results indicated that with the involvement of banks in implementing sustainable finance, banks must be selective in granting credit to debtors by setting conditions that are following bank policies. Because basically, sustainable finance activities do not harm the community, it creates justice for the community based on the constitutional rights of citizens to get a decent life. In the concept of sustainable finance, economic sustainability includes several criteria in carrying out credit risk analysis, including sustainability of resources, the sustainability of results and sustainability of the business.